Pathological conditions caused by magnesium deficiency in women at different ages - I S Zakharov; G A Ushakova; G I Kolpinskiy (IP Berlin A.V., 2015)
This paper presents a review of publications devoted to the conditions associated with magnesium deficiency in women. Considers the pathological processes occurring in different age and biological periods. Known role of the cation in the prevention of a number of obstetric complications such as premature labor, eclampsia, ischemic disorders of the central nervous system of the fetus. Well-grounded is the appointment of drugs of magnesium combined with vitamin B6 in the premenstrual tension syndrome, post-menopausal disorders. The complex of magnesium and pyridoxine has a protective effect by using combined hormonal contraception and menopausal hormone therapy, reducing the side effects of these drugs. The combination of magnesium drugs increases the efficiency of correction of osteoporosis. Thus, the use of magnesium-containing drugs in combination therapy to reduce the risk of some serious obstetric complications and help to cope with a number of states, reducing the quality of life of women.